Educational Tycoon Game and Cultural Heritage: Developing PAANTU BANG: Pasar Hantu Bangka - Amsana Rachmani, Almeera; Syahputra, Razen; Darmawan, Okki; Prayuda Wardani, Hastina; Amsana Rachmanio, Goldy; Faruq Vista, Umar (Bina Nusantara University, 2025)
With the rapid development of technology and digital information, video games have become a significant cultural phenomenon, with a rapidly growing number of players each year. Concerns regarding the impact of video games on mental health have been largely dismissed by recent studies, suggesting minimal negative effects and emphasizing the motivational aspects of gaming. Recognizing the potential of video games as educational tools, this study explores the development of